A Review of Ozone's Use in General Medicine and Dentistry (International Journal of Food and Nutritional Sciences, 2022)
Since more than a century ago, ozone, an allotropic form of oxygen, has been used to treat many ailments. It has many beneficial impacts on biological systems, including antibacterial, antihypoxic, analgesic, and immune stimulating properties. These methods of action, which are backed by numerous case reports and scientific investigations, enable its use in a variety of medical specialties. This literature study is an additional attempt to list the various methods of using ozone to dental problems. Standardizing the indications and treatment guidelines for this intriguing medicinal agent will require additional research.